E-services adoption processes by firms in developing nations - Quaddus, M. A.; Woodside, Arch G. (Advances in business marketing & purchasing, 2015)
Volume 23b includes two chapters covering problems and implementations of solutions in e-services adoption processes in developing nations. The first documents the unequal access and ICT usage, which is known as digital divide, to be one of the major obstacles to the implementation of e-government systems. This research investigates the digital divide and its direct impact on e-government system success of local governments in Indonesia as well as indirect impact through the mediation role of trust. To achieve a comprehensive understanding of digital divide, this study introduced a new type of digital divide, the innovativeness divide. It provides details for successful policy formulation to improve e-government readiness. The second explores what needs to be done to enable consumers to adopt e-services by airlines in developing nations. It includes new theory and empirical evidence from both qualitative and quantitative studies in response to this issue. Exciting and useful chapters for executives and researchers seeking knowledge and theory of how to influence e-service adoptions in developing nations!